Envisioning the ,,Right to Life and Enjoy Peace, Human Rights and Development" Within the Human Rigths Council - Fernandez, Christian Guillermet; Puyana, David Fernández (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
War and peace have perpetually alternated in history. Consequently, peace has always been seen as an endless project, even a dream, to be in brotherhood realized by all members of international community. Since the XVII century the elimination of war and armed conflict has been a political and humanitarian objective of all nations in the world. Both the League of Nations and the United Nations were conceived with the spirit of eliminating the risk of war through the pro¬motion of peace, cooperation and solidarity among Nations. The Universal Declaration of Hu¬man Rights and the subsequent human rights instruments were drafted with a sincere aspiration of promoting the value of peace and human rights worldwide. International practice shows the close linkage between the disregard of human rights and the existence of war and armed conflict. It follows that the role of human rights in the prevention of war and armed conflict is very important. Since 2008 the Human Rights Council has been working on the “Promotion of the right of peoples to peace.” Pursuant resolutions 20/15 and 23/16 and 27/17 the Council decided firstly to establish, and secondly and thirdly to extend the mandate of the openended working group (OEWG) aimed at progressively negotiating a draft United Nations declaration on the right to peace. The OEGW welcomed in its second session (July 2014) the approach of the Chairper- son-Rapporteur, which is basically based on the relationship between the right to life and human rights, peace and development. Consequently, this approach could be developed during the third session of the Working Group (April 2015). At its 8th meeting, on 24 April 2015, the Group adopted the draft report on its third session ad referendum and decided to entrust the Chairperson-Rapporteur with its finalization.

Wojna i pokój stale zmieniały bieg historii. W konsekwencji, pokój postrzegany był jako marzenie, niedokończony projekt, możliwy do osiągnięcia jedynie dzięki braterstwu wszystkich członków społeczności międzynarodowej. Od XVII wieku eliminacja wojny i konfliktów zbrojnych była politycznym i humanitarnym celem wszystkich narodów. Zarówno Liga Narodów, jak i Organizacja Narodów Zjednoczonych powołane zostały w dążeniu do wyeliminowania ryzyka konfliktów przez promocję pokoju, współpracy i solidarności między narodami. Powszechna Deklaracja Praw Człowieka i kolejne międzynarodowe akty prawne gwarantujące ochronę praw człowieka, przyjęte zostały jako wyraz dążenia do promowania wartości podstawowych, za jakie uznano pokój i prawa człowieka. Praktyka międzynarodowa pokazuje zależność między naruszaniem praw człowieka a pojawianiem się wojen i konfliktów zbrojnych. Jasnym jest więc, że w zapobieganiu konfliktom zbrojnym istotne znaczenie ma ciągłe podkreślanie wagi praw człowieka. Od 2008 r. Rada Praw Człowieka ONZ podejmuje prace nad promocją prawa człowieka do pokoju. W myśl rezolucji 20/15,23/16 i 27/17 Rada zdecydowała o ustanowieniu, a następnie o rozszerzeniu mandatu grupy roboczej (tzw. OEWG), której aktywność skierowana jest na opracowanie projektu deklaracji w prawie prawa do pokoju. Podczas drugiej sesji w lipcu 2014 r. eksperci zaakceptowali propozycję Przewodniczącego, wskazującą na związek między prawem do życia, prawami człowieka, pokojem i rozwojem. To podejście zostało rozwinięte podczas trzeciej sesji grupy roboczej w kwietniu 2015 r.
Uwzględnienie ,,prawa do życia w pokoju i korzystania z pokoju, do praw człowieka i do rozwoju" w pracach Rady Praw Człowieka ONZ